Stručné uvedení do policy analysis v kontextu sociální antropologie - Aleš Kavlír (AntropoWebzin, 2008)
The aim of this text is to briefly introduce practically oriented discipline called policy analysis, and to do so in the perspective of (applied) social anthropology.After the introductory definition of terms, which are crucial within the area of public policy, such as policy, policy studies, policy evaluation and policy analysis, I continue with the definition of the very policy analysis of which the explanation of its types and gradual steps towards reaching it are the necessary parts. Another part of the study summarizes the interrelation, interconnection and the enrichment of both disciplines – the policy analysis and the social and cultural anthropology. Several roles in which an anthropologist can assert himself/herself are presented in conclusion.